2018
DOI: 10.3390/rs10111851
|View full text |Cite
|
Sign up to set email alerts
|

Using TanDEM-X Pursuit Monostatic Observations with a Large Perpendicular Baseline to Extract Glacial Topography

Abstract: Space-based Interferometric Synthetic Aperture Radar (InSAR) applications have been widely used to monitor the cryosphere over past decades. Owing to temporal decorrelation, interferometric coherence often severely degrades on fast moving glaciers. TanDEM-X observations can overcome the temporal decorrelation because of their simultaneous measurements by two satellite constellations. In this study, we used the TanDEM-X pursuit monostatic mode with large baseline formation following a scientific phase timeline … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Another important factor to consider is the relative height accuracy of the DEM, which is specified as 2 m for flat terrain (slopes < 20°) and 4 m for mountainous regions (slopes > 20°) [62,63,86,87]. Regarding the interpretation of the data, this allows for some margin of error, as the accuracy of the InSAR Height measurements is strongly influenced by the relative height accuracy of the TanDEM-X data.…”
Section: Methodsmentioning
confidence: 99%
“…Another important factor to consider is the relative height accuracy of the DEM, which is specified as 2 m for flat terrain (slopes < 20°) and 4 m for mountainous regions (slopes > 20°) [62,63,86,87]. Regarding the interpretation of the data, this allows for some margin of error, as the accuracy of the InSAR Height measurements is strongly influenced by the relative height accuracy of the TanDEM-X data.…”
Section: Methodsmentioning
confidence: 99%
“…Hong et al [10], in their paper entitled "Using TanDEM-X Pursuit Monostatic Observations with a Large Perpendicular Baseline to Extract Glacial Topography", performed a feasibility test to construct high-resolution and high-precision topographic elevation models from TanDEM-X pursuit monostatic observations during the TanDEM-X Science Phase. For this study, the authors evaluated the measurement performance from more detailed topographic height variations along the moving surfaces of low slopes like glaciers.…”
Section: Remote Sensing Technology and Its Applicationsmentioning
confidence: 99%
“…In the 1990s, Dammert et al [23] demonstrated that InSAR technology has great value and potential in studying the backscattering characteristics of fast ice and sea ice mechanics models. In later studies, InSAR was successfully used to obtain sea ice motion maps in the Antarctic and develop highly precise topographic elevation models of glaciers [24,25]. InSAR has also provided information pertaining to landfast ice topography [14,16].…”
Section: Introductionmentioning
confidence: 99%